Flexible multilayered MXene/thermoplastic polyurethane films with excellent electromagnetic interference shielding, thermal conductivity, and management performances - Gao, Qingsen; Pan, Yamin; Zheng, Guoqiang; Liu, Chuntai; Shen, Changyu; Liu, Xianhu (Advanced composites and hybrid materials, 2021)
The prosperous development of smart wearable electronic devices has caused extensive demand for flexible composite films with integrated electromagnetic interference (EMI) shielding and thermal management performances. However, it is still a challenge to prepare flexible composite films with desirable properties. Herein, the flexible multilayered MXene/thermoplastic polyurethane films were prepared via a simple layer-by-layer spraying technique. The multilayered films with 28.6 wt% MXene and 52-µm thickness exhibit high electrical conductivity of 1600 S/m, excellent EMI shielding effectiveness of 50.7 dB in the X-band, and outstanding specific shielding effectiveness of 7276 dB.cm 2 g −1 . Meanwhile, a high in-plane thermal conductivity of 6.31 W/(m.k) and low cross-plane thermal conductivity of 0.42 W/(m.k) were obtained. Besides, the obtained films exhibit excellent Joule heating performance (113 °C) with low voltage (5 V), fast response time (< 10 s), excellent heating stability, and efficient de-icing as well as potential thermal stealth performance. Graphical abstract The multilayered MXene/TPU films were prepared by layer-by-layer spraying and exhibited excellent EMI shielding, thermal conductivity, and management performances.